Marinobacter: A case study in bioelectrochemical chassis evaluation. Issue 3 (4th December 2022) - Bird, Lina J.; Mickol, Rebecca L.; Eddie, Brian J.; Thakur, Meghna; Yates, Matthew D.; Glaven, Sarah M.
Abstract: The junction of bioelectrochemical systems and synthetic biology opens the door to many potentially groundbreaking technologies. When developing these possibilities, choosing the correct chassis organism can save a great deal of engineering effort and, indeed, can mean the difference between success and failure. Choosing the correct chassis for a specific application requires a knowledge of the metabolic potential of the candidate organisms, as well as a clear delineation of the traits, required in the application. In this review, we will explore the metabolic and electrochemical potential of a single genus, Marinobacter. We will cover its strengths, (salt tolerance, biofilm formation and electrochemical potential) and weaknesses (insufficient characterization of many strains and a less developed toolbox for genetic manipulation) in potential synthetic electromicrobiology applications. In doing so, we will provide a roadmap for choosing a chassis organism for bioelectrochemical systems. Abstract : The junction of bioelectrochemical systems and synthetic biology opens the door to many potentially groundbreaking technologies. When developing these possibilities, choosing the correct chassis organism can save a great deal of engineering effort and, indeed, can mean the difference between success and failure. In this review, we will explore the metabolic and electrochemical potential of the Marinobacter genus, suggesting applications to which these organisms may be best suited.